Thumb + Pen Interaction on Tablets - Pfeuffer, Ken; Hinckley, Ken; Pahud, Michel; Buxton, Bill (Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems (CHI '17), 2017)
Modern tablets support simultaneous pen and touch input, but it remains unclear how to best leverage this capability for bimanual input when the nonpreferred hand holds the tablet. We explore Thumb + Pen interactions that support simultaneous pen and touch interaction, with both hands, in such situations. Our approach engages the thumb of the device-holding hand, such that the thumb interacts with the touch screen in an indirect manner, thereby complementing the direct input provided by the preferred hand. For instance, the thumb can determine how pen actions (articulated with the opposite hand) are interpreted. Alternatively, the pen can point at an object, while the thumb manipulates one or more of its parameters through indirect touch. Our techniques integrate concepts in a novel way that derive from marking menus, spring-loaded modes, indirect input, and multi-touch conventions. Our overall approach takes the form of a set of probes, each representing a meaningfully distinct class of application. They serve as an initial exploration of the design space at a level which will help determine the feasibility of supporting bimanual interaction in such contexts, and the viability of the Thumb + Pen techniques in so doing.